Structure and Magnetization Dynamics of Dy−Fe and Dy−Ru Bonded Complexes. Issue 27 (30th May 2018) - Burns, Corey P.; Yang, Xin; Wofford, Joshua D.; Bhuvanesh, Nattamai S.; Hall, Michael B.; Nippe, Michael
Abstract: We present an investigation of isostructural complexes that feature unsupported direct bonds between a formally trivalent lanthanide ion (Dy 3+ ) and either a first‐row (Fe) or a second‐row (Ru) transition metal (TM) ion. The sterically rigid, yet not too bulky ligand PyCp2 2− (PyCp2 2− =[2, 6‐(CH2 C5 H3 )2 C5 H3 N] 2− ) facilitates the isolation and characterization of PyCp2 Dy−FeCp(CO)2 (1 ; d (Dy–Fe)=2.884(2) Å) and PyCp2 Dy−RuCp(CO)2 (2 ; d (Dy–Ru)=2.9508(5) Å). Computational and spectroscopic studies suggest strong TM→Dy bonding interactions. Both complexes exhibit field‐induced slow magnetic relaxation with effectively identical energy barriers to magnetization reversal. However, in going from Dy−Fe to Dy−Ru bonding, we observed faster magnetic relaxation at a given temperature and larger direct and Raman coefficients, which could be due to differences in the bonding and/or spin–phonon coupling contributions to magnetic relaxation. Abstract : First release : The first Dy−Fe and Dy−Ru bonded complexes have been synthesized and characterized both experimentally and computationally. This is also the first report of magnetization dynamics for any complex with lanthanide–transition‐metal bonding.